Microbial bile salt hydrolases mediate the efficacy of faecal microbiota transplant in the treatment of recurrent Clostridioides difficile infection. Issue 10 (11th February 2019) - Mullish, Benjamin H; McDonald, Julie A K; Pechlivanis, Alexandros; Allegretti, Jessica R; Kao, Dina; Barker, Grace F; Kapila, Diya; Petrof, Elaine O; Joyce, Susan A; Gahan, Cormac G M; Glegola-Madejska, Izabela; Williams, Horace R T; et al.
Abstract : Objective: Faecal microbiota transplant (FMT) effectively treats recurrent Clostridioides difficile infection (rCDI), but its mechanisms of action remain poorly defined. Certain bile acids affect C. difficile germination or vegetative growth. We hypothesised that loss of gut microbiota-derived bile salt hydrolases (BSHs) predisposes to CDI by perturbing gut bile metabolism, and that BSH restitution is a key mediator of FMT's efficacy in treating the condition. Design: Using stool collected from patients and donors pre-FMT/post-FMT for rCDI, we performed 16S rRNA gene sequencing, ultra performance liquid chromatography mass spectrometry (UPLC-MS) bile acid profiling, BSH activity measurement, and qPCR of bsh / bai CD genes involved in bile metabolism. Human data were validated in C. difficile batch cultures and a C57BL/6 mouse model of rCDI. Results: From metataxonomics, pre-FMT stool demonstrated a reduced proportion of BSH-producing bacterial species compared with donors/post-FMT. Pre-FMT stool was enriched in taurocholic acid (TCA, a potent C. difficile germinant); TCA levels negatively correlated with key bacterial genera containing BSH-producing organisms. Post-FMT samples demonstrated recovered BSH activity and bsh / bai CD gene copy number compared with pretreatment (p<0.05). In batch cultures, supernatant from engineered bsh -expressing E. coli and naturally BSH-producing organisms ( Bacteroides ovatus, Collinsella aerofaciens, Bacteroides vulgatus and Blautia obeum ) reduced TCA-mediated C. difficile germination relative to culture supernatant of wild-type (BSH-negative) E. coli. C. difficile total viable counts were ~70% reduced in an rCDI mouse model after administration of E. coli expressing highly active BSH relative to mice administered BSH-negative E. coli (p<0.05). Conclusion: Restoration of gut BSH functionality contributes to the efficacy of FMT in treating rCDI.